KEINDAHAN ILMU BADI’ DARI HADIS-HADIS PILIHAN DALAM ARBA’IN NAWAWI : (Studi Analisis Bahasa) - Habibi, Ahyat; Inanda Tsabithah Salsabila; Adi Aprianto (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
Arba'in Nawawi is a compilation of hadiths about the main teachings of Islam compiled by Yahya bin Sharaf An-Nawawi, or better known as Imam An-Nawawi. Nahwu scholars define hadith as the words of the Prophet shallallaahu 'alaihi wa salam, because the object of study is limited to his words. The Prophet had the specialty of jawami'ul kalim, which is a short utterances with perfect rhetoric while combining many meanings. Rhetoric or in Arabic called balaghoh is the suitability of sentences to situations or conditions. One branch of the science of balaghoh is Ilmu Badi’. Ilmu Badi’ is the science by which the beautiful aspects of a word are known after paying attention to the suitability and clarity of meaning. The method used is a qualitative approach with a library research type. The research results show a total of 80 forms of the beauty of Ilmu Badi’ in the Arba'in hadiths, 43 of them in terms of words and the remaining 37 in terms of meaning.